Economic Catastrophe Bonds - Coval, Joshua D; Jurek, Jakub W; Stafford, Erik (American Economic Review, 2009)
The central insight of asset pricing is that a security's value depends both on its distribution of payoffs across economic states and on state prices. In fixed income markets, many investors focus exclusively on estimates of expected payoffs, such as credit ratings, without considering the state of the economy in which default occurs. Such investors are likely to be attracted to securities whose payoffs resemble economic catastrophe bonds—bonds that default only under severe economic conditions. We show that many structured finance instruments can be characterized as economic catastrophe bonds, but offer far less compensation than alternatives with comparable payoff profiles. (JEL G11, G12)